Indicadores de provimento de serviços de saúde bucal no Brasil: análise longitudinal de 2016 a 2022 e comparação por porte populacional dos municípios - Bruno Antunes Ribeiro (2023)
Indicators are synthetic measures capable of determining the health condition of a population. This work aims to carry out a longitudinal analysis (2016-2022) of the performance of indicators for the provision of oral health services. This is an ecological study that used secondary data from the Health Information System for Primary Care (SISAB) regarding health/production reports for the period. The units of analysis were Brazilian municipalities with results stratified according to population size using data from the Brazilian Institute of Geography and Statistics. The outcomes are the indicators: proportion of clinical-surgical dental procedures, proportion of restorative dental procedures and proportion of individual preventive procedures in oral health , prepared based on the e-SUS APS Individual Dental Care Form and validated by the modified Delphi technique . A descriptive analysis of the performance of the indicators was carried out, creating the event variable to define pre- and post-pandemic periods. The results were presented in line graphs, with data for Brazil and the population sizes of the municipalities. The four-monthly variation was estimated using a regression model for longitudinal data, obtaining marginal estimates and applying the Wald Test. For data analysis, Stata ® 18.0 software was used. The results demonstrate that the values of the indicators did not change much until Quadrimester (QD) 1 2020, in the pre -pandemic period. The indicators changed from QD2 2020, when the proportion of clinical-surgical procedures increased significantly and the proportion of restorative procedures suffered a significant drop. The indicator of preventive procedures predominated in Brazil and in all population sizes, except in smaller municipalities, throughout the period. The indicators varied depending on the population size/quarter/event interaction . In municipalities with a population of up to 9,900 inhabitants, the reduction in restorative procedures was significant after the pandemic and the increase in clinical surgical procedures was significant for all population sizes after the event. It is concluded that there are differences in the performance of the indicators between population sizes and in the pre- and post-COVID-19 pandemic period. Concomitantly with the quantitative study, three technical products were developed: (i) the Dictionary of Indicators for the Assessment of Oral Health Services in Primary Health Care in e-book format, which describes in detail the indicators evaluated by this study and the others that make up the evaluation matrix; ( ii ) the Indicator Panel for monitoring Oral Health Services in Primary Health Care, freely accessible via URL, consisting of a strategy for incorporating unprecedented digital technology to generate information through health indicators oral health from records in e-SUS APS, with results demonstrated through graphs, maps and tables and ( iii )the Oral Health Indicator Calculator, made available freely and online for managers and Oral Health Teams to calculate the indicators with local production data from the teams.